A Literature Review: Detection of COVID-19 in Computed Tomography Images Using Deep Learning - Marques, Júlio V. M.; Veras, Rodrigo M. S.; Silva, Romuere R. V. (Anais do Encontro Unificado de Computação do Piauí (ENUCOMPI); 2021: Anais do XIV Encontro Unificado de Computação do Piauí e XI Simpósio de Sistemas de Informação, 2021)
Through the development of the COVID-19 disease, various diagnosis methods have been studied. One of them is the computed tomography (CT), which has the best level of detail among medical image exams. The CT generates a repeatable and tiring workload, in addition to needing a team that is familiar with the findings that indicate pneumonia caused by COVID-19. To reduce this manual work and collaborate with these teams, several studies have been carried out using deep learning techniques. In this way, this study presents a review of the literature regarding the detection of COVID-19 in CT that uses deep learning to collaborate with a theoretical basis for future works.